Strategi Marketing Public Relations dalam Mengelola Loyalitas Pelanggan: Studi Kasus Pada Strategi Marketing Public Relations “Café Beda Cerita Coffee Bandung” Dalam Mengelola Loyalitas Pelanggan - Nadiskha Putri Fadillah; Maman Suherman (Bandung Conference Series: Public Relations, 2023)
Abstract. The culinary business industry in the coffee shop sector has mushroomed in every corner of the city. The rise of the coffee shop business has resulted in intense market competition for coffee entrepreneurs. This market competition is also experienced by Café Beda Cerita, this requires Beda Cerita to be able to compete and continuously innovate and improvise in an effort to manage customer loyalty through an unusual strategy. Managing customer loyalty is quite difficult because it requires a well-planned strategy to build trust and build a good image that is well known to many people. Loyalty is formed from service as well as the company's image in fulfilling the wants and needs of customers, so that Different Stories implements Marketing Public Relations to manage one of its assets, namely loyal customers. The purpose of this research is to find out and describe the Marketing Public Relations strategy used by Different Stories in managing customer loyalty. In this study, researchers used qualitative research methods with a case study approach. The paradigm used is constructivism. Conducting in-depth interviews with MPR Different Stories, researchers used secondary data as triangulation. The results showed that the MPR strategy was carried out in the planning stage with situation analysis, the implementation stage was with a strategy to attract attention (publication), a strategy to stimulate purchases, and a strategy to form public opinion, the last stage was evaluation by opening up interaction space as an evaluation material from customers. Obstacles in the service aspect occur in internal and external factors. Different Stories overcome obstacles by implementing customer relations. The reasons for using MPR activities are based on efficiency and the long-term impact of establishing good relations with customers. Abstrak. Industri bisnis kuliner pada bidang coffee shop saat ini sudah menjamur disetiap sudut kota. Maraknya bisnis coffee shop menimbulkan ketatnya persaingan pasar bagi para pengusaha kopi. Persaingan pasar tersebut dialami juga oleh Café Beda Cerita, hal ini mengharuskan Beda Cerita mampu bersaing dan secara terus-menerus berinovasi dan berimprovisasi dalam upaya mengelola loyalitas pelanggan melalui strategi yang tidak biasa. Mengelola loyalitas pelanggan cukup sulit karena membutuhkan strategi yang terencana untuk menumbuhkan rasa percaya dan membangun citra yang baik juga dikenal orang banyak. Loyalitas terbentuk dari pelayanan juga citra perusahaan dalam memberikan keinginan dan kebutuhan pelnggan, dengan begitu Beda Cerita menerapkan Marketing Public Relations untuk mengelola salah satu aset yang dimiliki yaitu pelanggan loyal. Tujuan penelitian ini adalah untuk mengetahui dan menjabarkan strategi Marketing Public Relations yang digunakan Beda Cerita dalam mengelola loyalitas pelanggan. Dalam penelitian ini peneliti menggunakan metode penelitian kualitatif dengan pendekatan studi kasus. Paradigma yang digunakan yaitu konstruktivisme. Melakukan wawancara mendalam dengan MPR Beda Cerita, peneliti menggunakn data sekunder sebagai triangulasi. Hasil penelitian menunjukan strategi MPR dilakukan dengan tahap perencanaan dengan analisis situasi, tahap pelaksanaan dengan strategi menarik perhatian (publikasi), strategi merangsang pembelian, dan strategi membentuk opini publik, tahap terahir yaitu evaluasi dengan membuka ruang interaksi sebagai bahan evaluasi dari pelanggan. Hambatan dalam aspek pelayanan terjadi pada faktor internal dan eksternal Beda Cerita mengatasi hambatan dengan menerapan customer relations. Alasan menggunakan aktivitas MPR didasari akan efisien dan dampak jangka panjang menjalin hubungan baik dengan pelaggan.